Pemanfaatan Media Poster Abjad Sebagai Upaya Peningkatan Kemampuan Pengenalan Huruf Siswa Penyandang Tuna Grahita di SLB Negeri Siborong-borong - Putri O. Hutasoit; Benida D. Nababan; Masri Sagala; Monica Silitonga; Punia L. M. Sihombing; Maria Widiastuti (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Abstract: Based on the results of observations at the Siborong-borong State SLB, the team found that mentally retarded students could imitate the writing made by their teacher, but these students did not know what they were writing, let alone read, they did not know the letters. So, the team tried to introduce letters to students by applying the alphabetical poster method, with the hope that mentally retarded students would be able to recognize letters. The purpose of using alphabetical poster media in the teaching and learning process is to improve the letter recognition skills of mentally retarded students at Siborong-borong State SLB. This research was conducted by making observations first then the observation data were collected to plan the implementation of learning, then carry out the teaching and learning process by applying the alphabetical poster method. The subject of this learning process is students with special needs for mental retardation at Siborong-borong State SLB. This teaching and learning process is carried out every Monday from October to November. The learning process activity by applying the alphabetical poster method at the Siborong-borong State SLB is carried out to provide motivation for letter recognition to students. Based on the learning process activities by applying the alphabetic poster method carried out by the team in the mentally retarded class at Siborong-borong State SLB, it turn out that this method is indeed able to improve letter recognition skills among mentally retarded students by attracting students' attention with alphabetic posters, then the teacher introduces it with terms (for example: the letter B = a stick plus two stomachs), so that students are able to recognize the letters gradually. During October-November the team carried out learning practices using this method, it can be seen that the ability of mentally retarded students is able to recognize all the letters well, but because they are "with special needs who have weak memory and reception of information", they must be trained always so they do not forget. From the community service activities for female students of Christian Religious Education Study Program semester 5 at IAKN Tarutung which are carried out at the Siborong-borong State SLB through teaching practice in mentally retarded classes with the application of the alphabetic poster method, it can be concluded that the alphabetic posters used can help improve students' letter recognition skills / i mentally impaired.